2014
DOI: 10.1002/anie.201405442
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4‐Targeted and MMP‐Responsive Iron Oxide Nanoparticles for Enhanced Magnetic Resonance Imaging

Abstract: MRI offers high spatial resolution with excellent tissue penetration but it has limited sensitivity and the commonly administered contrast agents lack specificity. In this study, two sets of iron oxide nanoparticles (IONPs) were synthesized that were designed to selectively undergo copper-free click conjugation upon sensing of matrix metalloproteinase (MMP) enzymes, thereby leading to a self-assembled superparamagnetic nanocluster network with T2 signal enhancement properties. For this purpose, IONPs with bioo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(78 citation statements)
references
References 41 publications
0
78
0
Order By: Relevance
“…For example, such a self-assembly strategy allows for small NPs to circulate in the blood pool over a prolonged time duration, which can then be triggered in the tumor to self-assemble into a large structure for enhanced MRI. The trigger may include many physiological characteristics, such as molecular interactions, 195 enzymes, 196 receptors, 197 and redox status. 198 On the other hand, the disassembly strategy utilizes the different tumor microenvironments to release CAs preconfined in NPs, also achieving amplified MRI contrast.…”
Section: Strategies To Achieve High Relaxivity For Mri Contrast Enmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, such a self-assembly strategy allows for small NPs to circulate in the blood pool over a prolonged time duration, which can then be triggered in the tumor to self-assemble into a large structure for enhanced MRI. The trigger may include many physiological characteristics, such as molecular interactions, 195 enzymes, 196 receptors, 197 and redox status. 198 On the other hand, the disassembly strategy utilizes the different tumor microenvironments to release CAs preconfined in NPs, also achieving amplified MRI contrast.…”
Section: Strategies To Achieve High Relaxivity For Mri Contrast Enmentioning
confidence: 99%
“…Mao and co-workers reported that ultrafine iron oxide NPs (~3.5 nm) with high T 1 relaxivity exhibited prolonged in vivo circulation life time and could be self-assembled or clustered into larger ones in the tumor, thereby switching from bright T 1 contrast to dark T 2 contrast in MRI. 205 In another report, two complementary iron oxide NPs that were linked to a peptide substrate for enzymatic cleavage and a functional group (azide or alkyne) for click reaction 196 were able to self-assemble into a larger nanocluster network in the presence of matrix metalloproteinase enzymes, leading to approximately 160% enhancement of T 2 signal intensity.…”
Section: Strategies To Achieve High Relaxivity For Mri Contrast Enmentioning
confidence: 99%
“…29 In their study, two types of IONPs-based, CXCR4 receptor targeted nanoparticles were conjugated with either azide or alkyne functional groups. Both IONPs were conjugated with protease-specific peptide sequence, which was cleavable by MMP enzymes in MMP2/6 overexpressing tumors.…”
Section: Copper-free Azide-alkyne Click Reactionmentioning
confidence: 99%
“…[1] Of these, magnetic resonance imaging (MRI) has attracted much attention because of its noninvasive and nonradiative properties and high contrast and resolution in soft tissues. [11,12] It has been proved that magnetization and size of SPIO NPs significantly contributed to the transverse relaxation rate (R 2 ) of proximal water protons, and higher magnetic fields generally lead to larger R 2 values. [6][7][8] Conventional CAs are roughly divided into two categories, longitudinal (T 1 ) CAs and transverse (T 2 ) CAs.…”
Section: Introductionmentioning
confidence: 99%